2009
DOI: 10.1029/2009rs004186
|View full text |Cite
|
Sign up to set email alerts
|

Plasmasphere effects for GPS TEC measurements in North America

Abstract: [1] Plasmasphere effects on total electron content (TEC) measurements conducted using Global Positioning System (GPS) receivers are typically neglected for the North American region, because of the relatively high magnetic latitudes there, but model and measurement cases for this region are presented here to demonstrate the magnitude of the effects for GPS TEC measurements away from vertical and for the associated equivalent vertical TEC values. For high solar flux conditions, the effects of high, distant elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 17 publications
7
34
0
2
Order By: Relevance
“…Ciraolo and Spalla 1997) with further discussion of the effects of the layer above 1,000 km in e.g. (Mazzella 2009). For more detailed information on the ionosphere, see e.g.…”
Section: Characteristics and Variabilitymentioning
confidence: 98%
“…Ciraolo and Spalla 1997) with further discussion of the effects of the layer above 1,000 km in e.g. (Mazzella 2009). For more detailed information on the ionosphere, see e.g.…”
Section: Characteristics and Variabilitymentioning
confidence: 98%
“…One might be able to adjust for this error by increasing the projection shell height; however, as shown in Table 2 with the true CM height, the high degree of asymmetry in the profile results in new errors in estimated bias. This leaves operators of middle-and low-latitude stations with a significant challenge in their bias estimation, as pTEC can exceed 10 TECU at those locations [Lunt et al, 1999a;Mazzella, 2009]. Jan, 2009Jan, 2010Jan, 2011Jan, 2012Jan, 2013 Date 30 This mechanism has been extensively researched in the works of Lunt et al [1999aLunt et al [ , 1999b, Mazzella et al [2002], and Mazzella [2009].…”
Section: Plasmaspheric Electron Contentmentioning
confidence: 99%
“…This leaves operators of middle-and low-latitude stations with a significant challenge in their bias estimation, as pTEC can exceed 10 TECU at those locations [Lunt et al, 1999a;Mazzella, 2009]. Jan, 2009Jan, 2010Jan, 2011Jan, 2012Jan, 2013 Date 30 This mechanism has been extensively researched in the works of Lunt et al [1999aLunt et al [ , 1999b, Mazzella et al [2002], and Mazzella [2009]. While this is a significant concern for midlatitude observations, the absence of an appreciable plasmasphere in the polar cap region [Lunt et al, 1999a;Nsumei et al, 2008] debunks this as a mechanism through which the observed biases, and thus the ISR-GPS comparisons, should vary at the Resolute site.…”
Section: Plasmaspheric Electron Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Other research has found that the distribution of the plasmaspheric electron content along the meridional line has a significant effect on TEC and GPS instrumental bias estimation, and the accuracy of the instrumental bias can be improved by properly considering the distribution of the plasmaspheric electron content (Lunt et al, 1999;Mazzella et al, 2002Mazzella et al, , 2007Mazzella et al, , 2009Anghel et al, 2009;Carrano et al, 2009). Based on this improvement the distribution of the plasmaspheric electron content was estimated using GPS measurements (Mazzella et al, 2002(Mazzella et al, , 2007Anghel et al, 2009;Carrano et al, 2009).…”
Section: Results and Analysismentioning
confidence: 99%